EVALUASI STATUS HARA BAHAN ORGANIK TERHADAP SIFAT KIMIA TANAH DI LAHAN MIRING KELAPA SAWIT - Hilwa Walida; Fitra Syawal Harahap; Zuriani Ritongah; Pitri Yani; Rendi Fitra Yana (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2020)
This study aims to identify the fertility variable that is an obstacle in Bilah Hulu Subdistrict, Labuhanbatu Regency by evaluating the status of soil fertility and assessing alternative management in accordance with the status of soil fertility found in the Center of the People's Palm Oil Plantation, N Satu Aek Nabara Village, Bilah Hulu District, Labuhanbatu Regency with a height of ± 80 meters above sea level. This research is a phenomenological qualitative descriptive study with a land survey and is supported by a qualitative laboratory analysis. Soil sampling is carried out in the survey area sequentially based on where the estimated nature of the soil is different from the purposive random sampling method, so the results of the soil analysis obtained are expected to reflect the true value. 60 cm and recording the coordinates using global Positioning System. Whereas soil management information is obtained by direct field observation and in-depth interviews with farmers in a snow ball aiming to obtain complete information from farmers. Soil chemical properties analyzed in C-organic laboratory, CEC, Base Saturation. To determine the chemical properties of the soil with certain criteria that have been determined. Based on Technical Instructions for Evaluating Soil Fertility. Soil fertility parameters that become obstacles in the status of soil fertility in N Satu Aek Nabara Village, Bilah Hulu District, Labuhanbatu Regency are low soil organic matter content and very low soil fertility. The direction of management of soil fertility for sloping land units in the lower, palm, and peak areas of palm oil is in the form of adding organic matter with compost and fertilizer and inorganic substances in accordance with recommendations to improve soil fertility status.